Challenging constraints or constraining challenges: Preservice primary music education across the Tasman - Robyn Margaret Trinick; Dawn Joseph (New Zealand Journal of Teachers' Work)
Tertiary music educators are faced with challenges associated with the enactment of curricula in pre-service education courses within time constraints.  As a result, considered choices need to be made regarding content and pedagogical approaches based on what they deem to be valuable, memorable and transferrable. Using narrative methodology, two tertiary educators across the Tasman share their views about what they prioritise in their music education courses and how these choices are informed.  Both authors face similar challenges, and share the view that the teaching of music goes far beyond entertainment.  They uphold that music education provides a rich context to develop not only knowledge, skills and understandings about music itself, but also to address social, cultural, linguistic, cognitive and affective domains of learning, to name a few.  This article looks at some of the ways the authors effectively support beginner teachers to address the music components of their respective national curriculum statements.  While constraints of time in teacher education programmes is not a new phenomenon, the intention of this article is to highlight the benefits of music education, and encourage other educators to critically reflect on choices made in their own teaching contexts under challenging constraints.